Exploration of DFT and Hirshfeld analyses and fluorescence properties of three stable penta-coordinated binuclear Co(II) and Zn(II) bis(salamo)-based complexes. (1st September 2021) - Li, Li-Li; Li, Peng; Zhang, Ting; Dong, Wen-Kui
Graphical abstract: A newly designed symmetrical multi-halogen-substituted bis(salamo)-based tetraoxime ligand H3 L and its three penta-coordinated homo-binuclear Co(II) and Zn(II) complexes have been successfully synthesized and characterized structurally. Hirshfeld surfaces, DFT calculations and luminescences of the three complexes were investigated in detail. Abstract: A new symmetrical multi-halogen-substituted bis(salamo)-based tetraoxime ligand H3 L and its corresponding penta-coordinated homo-binuclear Co(II) and Zn(II) complexes have been successfully synthesized. The three complexes, [Co2 (L)(OCH3 )2 ]·CHCl3 (1 ), [Zn2 (L)(OCH3 )2 ]·CH3 OH (2 ) and [Co2 (L)(OCH2 CH3 )3 ]·2CH3 CH2 OH·CHCl3 (3 ), have been characterized by elemental analyses, FT-IR and UV–Vis absorption spectroscopy as well as X-ray single-crystal structure analyses. In complexes 1 and 2, two crystallographically independent but chemically identical binuclear complex molecules A and B were detected by X-ray analysis. However, in complex 3, three crystallographically independent but chemically identical binuclear complex molecules A, B and C were detected. All the penta-coordinated Co(II) and Zn(II) atoms in complexes 1 and 2 are located in the N2 O2 cavities of the completely deprotonated (L) 3- units and coordinated to one oxygen atom from one μ 2 -bridged methoxyl group. The coordination environment of the Co(II) atoms in complexes 1 and 3 are similar, except that the μ 2 -bridged methoxyl group is replaced with the μ 2 -bridged ethoxyl group. Additionally, both of complexes 1 and 3 form 3D supramolecular structures through abundant intermolecular interactions, while complex 2 forms 1D supramolecular structure through intermolecular hydrogen bonds. The CH···π interactions have been established in complexes 1 and 2, where the π-system of H3 L participates as π-donor. Through the means of Hirshfeld surfaces and 2D fingerprint plot analyses, existing different non-covalent supramolecular interactions in the Co(II) and Zn(II) complexes have been explained. Furthermore, to obtain a better understanding of the fluorescence properties of H3 L and its complexes 1 –3, fluorescence titration experiments have been performed.